2023
DOI: 10.1002/pc.27258
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized ZnO nanoflake loaded polyvinylidene fluoride composites with enhanced energy storage properties

Abstract: Polymer composite films are ideal materials for advanced energy storage capacitor in electrical systems. Therefore herein, we fabricated a novel series of polyvinylidene fluoride (PVDF) based composites embedded with well dispersed ZnO@APTES {surface modified zinc oxide with (3‐Aminopropyl) triethoxysilane (APTES)} nanoflake (0, 20, 30, 40, 50) vol% through solution casting method. Hydrothermally synthesized two‐dimensional ZnO was pre‐treated with H2O2 and surface modified with APTES for perfect distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Most of the time, silanes are first bonded to ceramic fillers to promote dispersion and stabilize the suspension of the particles in the solvent. A pre‐treatment of ceramic fillers with H 2 O 2 can be performed 143 . Alkoxy‐silanes are well known to form strong bonds with ceramic surfaces via condensation reactions (Figure 3).…”
Section: Addition Of Ca At the Ceramic/polymer Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time, silanes are first bonded to ceramic fillers to promote dispersion and stabilize the suspension of the particles in the solvent. A pre‐treatment of ceramic fillers with H 2 O 2 can be performed 143 . Alkoxy‐silanes are well known to form strong bonds with ceramic surfaces via condensation reactions (Figure 3).…”
Section: Addition Of Ca At the Ceramic/polymer Interfacementioning
confidence: 99%
“…A pre-treatment of ceramic fillers with H 2 O 2 can be performed. 143 Alkoxy-silanes are well known to form strong bonds with ceramic surfaces via condensation reactions (Figure 3). Silane CAs were used by Runt et al in 1-3 PZT/epoxy composite, 144 and were shown to improve the stress transfer in the composite and thus, the piezoelectric activity.…”
Section: Silane Casmentioning
confidence: 99%
“…Different techniques like surface modification of fillers [ 21 ], formation of core-shell fillers [ 22 ], etc., have been explicitly explored in this regard in order to strengthen this interfacial interaction and hence improve the polarity of PVDF-based composites [ 21 , 22 , 23 ]. These surface or interface modification techniques require difficult chemical routes.…”
Section: Introductionmentioning
confidence: 99%
“…NZnO has a low particle size and high surface area (7-10 m 2 /g) based on the method of synthesis and these factors can facilitate the vulcanization reaction by offering an abundance of active sites. 20 In addition, the nanoparticles' tiny size permits improved dispersion within the rubber matrix at lower phr loading, resulting in a more uniform crosslinking density and enhanced mechanical qualities of the final blend. NZnO can be a highly effective activator in SBR/NR blends, resulting in enhanced mechanical characteristics and overall blend performance.…”
Section: Introductionmentioning
confidence: 99%
“…NZnO can improve the mechanical qualities of SBR/NR blends, such as tensile strength and elongation at break. NZnO has a low particle size and high surface area (7–10 m 2 /g) based on the method of synthesis and these factors can facilitate the vulcanization reaction by offering an abundance of active sites 20 . In addition, the nanoparticles' tiny size permits improved dispersion within the rubber matrix at lower phr loading, resulting in a more uniform crosslinking density and enhanced mechanical qualities of the final blend.…”
Section: Introductionmentioning
confidence: 99%